Thermal and energy performance of algae bioreactive façades: A review. (March 2020) - Talaei, Maryam; Mahdavinejad, Mohammadjavad; Azari, Rahman
Abstract: Algae convert sunlight and carbon dioxide into oxygen, heat, and biomass. The integration of microalgae, as a photobioreactor-based source of biofuel, with buildings, has the potential to transform high-performance architecture. This article will review the state-of-the-art knowledge on microalgae bioreactive facades, provide a survey of previous studies regarding the performance of these innovative façade systems, present the status quo and identify the gaps in theory and applications of these systems. We also compare microalgae bioreactive facades with green walls and double skin facades (DSF) and discuss these systems from thermal, shading, and natural ventilation perspectives. Finally, the performance of microalgae facades as solar thermal collectors is discussed and some recommendations for future research are presented. Highlights: Comprehensively reviewing the thermal and energy performances of microalgae bioreactive facade. Identifying the gap in theory and application of this innovative façade system. Making a comparison between microalgae bioreactive façade, green wall, and double skin facades. Proposing recommendations for applying this system and future researches.